Clinical researchDifferent diagnostic criteria significantly affect the rates of hypertension in 18-year-old high school students - Symonides, Bartosz; Jędrusik, Piotr; Artyszuk, Łukasz; Gryboś, Anna; Dziliński, Paweł; Gaciong, Zbigniew (Archives of Medical Science, 2010)
Introduction : Childhood hypertension is defined based on the normative distribution of blood pressure (BP), but from the age of 18 years high BP is diagnosed using adult criteria. We compared the rates of diagnosis of hypertension in a group of 18-year-old subjects using BP percentiles and the adult criteria. Material and methods : Blood pressure was measured by registered nurses in 1472 18-year-old high-school students (780 men and 692 women). Also weight, height and waist circumference were recorded. Results : The prevalence of hypertension was 9% (16.2% in men and 0.9% in women, p < 0.001) using adult cut-off values and 14.7% (21.9% in men and 6.6% in women, p < 0.001) using percentile charts. Obesity was diagnosed in 2.4% and overweight in 13% of subjects, respectively. The relative risk ratio of diagnosing hypertension according to the adult criteria in overweight or obese subjects was 2.94 (95% CI 2.25-3.86) in men and 6.44 (95% CI 3.51-11.82) in women. Conclusions : Our study indicates high prevalence of hypertension in 18-year-old students – especially in men – and the importance of obesity as a risk factor of hypertension. The use of percentile charts instead of adult cut-off values increases the prevalence of hypertension in men by 35% from 16.2% to 21.9% and in women more than 7 times, i.e. from 0.9% to 6.6%. It seems reasonable to use higher (i.e. 98th) percentile values for definition of high blood pressure.